Chemical and Sensory Profiling of Monovarietal Extra Virgin Olive Oils from the Italian Marche Region - Deborah Pacetti; Maria Chiara Boarelli; Rita Giovannetti; Stefano Ferraro; Paolo Conti; Barbara Alfei; Giovanni Caprioli; Massimo Ricciutelli; Gianni Sagratini; Donatella Fedeli; Rosita Gabbianelli; Dennis Fiorini (MDPI AG, 2020)
Chemical and sensory peculiarities of monovarietal extra virgin olive oils (MEVOOs) from the cultivars (cvs.) Ascolana tenera (ASC), Coroncina (COR), Mignola (MIG), Piantone di Mogliano (MOG), and Raggia (RAG) from Marche region (Italy) are investigated. Their polar phenolic substances and α-tocopherol are analysed through high performance liquid chromatography with different detectors. Volatile substances, fatty acid composition, and squalene are analysed by gas chromatography coupled to mass spectrometry (MS) and to the flame ionization detector, respectively. Total antioxidant activity and sensory analysis were also performed. MOG showed high squalene content (on average 0.88 ± 0.16 g/100 g), high relative amount of α-copaene among volatiles, and the highest oleic acid percentage. MIG had high α-tocopherol content (on average 350.0 ± 57.6 mg kg−1) and high α-farnesene in the volatile fraction. ASC showed the highest sensory quality and the lignan pinoresinol with higher concentration as compared to the other MEVOOs (p < 0.05), which resulted in a possible chemical marker for this cv. RAG was characterized by the sensory note of almond, which corresponds to its highest (E)-2-hexenal percentage. Sensory analysis and an antioxidant activity assay performed on a set of industrial extra virgin olive oils purchased in supermarkets, highlighted MEVOOs' superiority from these points of view. Principal component analysis displays the main characteristics of the cvs. investigated.